Zinc oxide formation in galvanized metallic wire by simple selective growth method. (June 2015) - A., Sivanantham; C., Abinaya; V., Vishnukanthan; P., Jayabal; K., Boobalan; S., Mohanraj; Mayandi, J.
Highlights: It is a simple and cost effective method for the preparation of ZnO. Magnetic properties were discussed. Growth mechanism was proposed. Abstract: ZnO nanostructures were synthesized by a simple method of oxidizing metallic wire by direct electrical heating. A galvanized iron wire was used as the source of zinc. Several optical techniques were employed on the synthesized ZnO nanostructure such as photoluminescence, Raman and FTIR spectroscopy. The formation of ZnO nanostructures was confirmed from the spectra of different optical studies and also determined by XRD. SEM analysis shows the signature of nanorod formation on the surface of the wire. The oxidation state and ferromagnetic property of these oxidized metallic wires were discussed with the help of EPR spectrum. In summation to the properties studied, a growth mechanism was suggested based on the observations and method of the oxidation procedure.